The correlation between sperm percentage with a small acrosome and unexplained in vitro fertilization failure - Chuyan Li; Ya Ni; Lingnv Yao; Jiajie Fang; Nan Jiang; Jing Chen; Wenqin Lin; Hanchen Ni; Haiyan Zheng (BMC, 2024)
Abstract Purpose Since the unexplained in vitro fertilization failure occurs frequently, it is of great importance and clinical value to identify potential underlying predictors. This study aimed to explore whether the percentage of sperm with a small acrosome was correlated with unexplained in vitro fertilization failure. Methods A new acrosomal function evaluation index (the percentage of sperm with a small acrosome) was introduced into the analysis of sperm morphology. The association between the index and acrosome function by acrosin activity detection test and acrosome reaction test was investigated. In addition, the correlation with unexplained in vitro fertilization failure was further explored. Finally, the ROC curve was used to analyze the diagnostic efficacy on the failure of in vitro fertilization and the cutoff value was calculated. Results As the increasing of the percentage of sperm with a small acrosome, the value of acrosin activity, acrosome reaction rate, and in vitro fertilization rate were reduced, with a statistically significant difference (P < 0.05). The index in the low fertilization rate group was significantly higher than that in the normal fertilization rate group (P < 0.05). Finally, the results of ROC curve found that when the index was 43.5%, the sensitivity and specificity were 74.2% and 95.3%, respectively. Conclusion The percentage of sperm with a small acrosome was positively correlated with unexplained in vitro fertilization failure, which could be potentially used as a prognostic index for the failure of in vitro fertilization. Trial registration [Ethics review acceptance No IIT20210339B]